2021
DOI: 10.3390/ijms22168936
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine/Cyclophosphamide Synergism on Chemoresistant Neuroblastoma Models

Abstract: Neuroblastoma (Nb), the most common extracranial tumor in children, exhibited remarkable phenotypic diversity and heterogeneous clinical behavior. Tumors with MYCN overexpression have a worse prognosis. MYCN promotes tumor progression by inducing cell proliferation, de-differentiation, and dysregulated mitochondrial metabolism. Cyclophosphamide (CFF) at minimum effective oral doses (metronomic therapy) exerts beneficial actions on chemoresistant cancers. Molecular iodine (I2) in coadministration with all-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…391 It is a prodrug, forming amino[bis(2chloroethyl)amino]phosphinic acid, which is an active antineoplastic ingredient, and acrolein (prop-2-enal), which is associated with side effects. Clinical studies have been initiated with other substances, such as iodine, 392 and drugs for advanced or metastatic breast cancer patients and mature B-cell non-Hodgkin lymphoma in children carrying wt and mutant p53. A recent CT enrolled patients with solid tumors and relapsed AML for clinical treatment with atorvastatin to decrease the mutant p53 protein levels.…”
Section: Targeting P53 L1/s3 and Y220c Mutant To Restore Wt P53 Functionmentioning
confidence: 99%
“…391 It is a prodrug, forming amino[bis(2chloroethyl)amino]phosphinic acid, which is an active antineoplastic ingredient, and acrolein (prop-2-enal), which is associated with side effects. Clinical studies have been initiated with other substances, such as iodine, 392 and drugs for advanced or metastatic breast cancer patients and mature B-cell non-Hodgkin lymphoma in children carrying wt and mutant p53. A recent CT enrolled patients with solid tumors and relapsed AML for clinical treatment with atorvastatin to decrease the mutant p53 protein levels.…”
Section: Targeting P53 L1/s3 and Y220c Mutant To Restore Wt P53 Functionmentioning
confidence: 99%
“…To explore the role of TAF1D in tumors, we established subcutaneous xenografts in BALB/c‐nude mice using SK‐N‐BE(2) cells infected with TAF1D ‐targeting or control shRNA as previously described 28 . TAF1D knockdown with either validated shRNA resulted in significantly smaller tumors compared with controls (Figure 5A–E).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the role of TAF1D in tumors, we established subcutaneous xenografts in BALB/c-nude mice using SK-N-BE(2) cells infected with TAF1D-targeting or control shRNA as previously described. 28 TAF1D knockdown with either validated shRNA resulted in significantly smaller tumors compared with controls (Figure 5A-E). In agreement with our in vitro data, immunohistochemical staining showed that the proliferation marker, Ki-67, 29 was significantly lower in tumors from both TAF1D-knockdown groups compared with the control (Figure 5F).…”
Section: Taf1d Knockdown Limits the Growth Of Mycn-amplified Nb Tumorsmentioning
confidence: 96%
“…Most children with intermediate-risk and high-risk neuroblastoma will need to have chemotherapy and cyclophosphamide is one of the commonly used drugs [21][22][23][24]. We intend to explore whether the environment influences the tumor cell characteristics and the subsequent drug sensitivity after long time growth in orthotopic and subcutaneous mice, therefore, we reinoculated the tumor cells to different sites such as Ortho to Subq and Subq to Ortho.…”
Section: Discussionmentioning
confidence: 99%